Temporal mapping of CEBPA and CEBPB binding during liver regeneration reveals dynamic occupancy and specific regulatory codes for homeostatic and cell cycle gene batteries - Jakobsen, Janus Schou; Waage, Johannes; Rapin, Nicolas; Bisgaard, Hanne Cathrine; Larsen, Fin Stolze; Porse, Bo Torben (Genome Research, 2013)
Dynamic shifts in transcription factor binding are central to the regulation of biological processes by allowing rapid changes in gene transcription. However, very few genome-wide studies have examined how transcription factor occupancy is coordinated temporally in vivo in higher animals. Here, we quantified the genome-wide binding patterns of two key hepatocyte transcription factors, CEBPA and CEBPB (also known as C/EBPalpha and C/EBPbeta), at multiple time points during the highly dynamic process of liver regeneration elicited by partial hepatectomy in mouse. Combining these profiles with RNA polymerase II binding data, we find three temporal classes of transcription factor binding to be associated with distinct sets of regulated genes involved in the acute phase response, metabolic/homeostatic functions, or cell cycle progression. Moreover, we demonstrate a previously unrecognized early phase of homeostatic gene expression prior to S-phase entry. By analyzing the three classes of CEBP bound regions, we uncovered mutually exclusive sets of sequence motifs, suggesting temporal codes of CEBP recruitment by differential cobinding with other factors. These findings were validated by sequential ChIP experiments involving a panel of central transcription factors and/or by comparison to external ChIP-seq data. Our quantitative investigation not only provides in vivo evidence for the involvement of many new factors in liver regeneration but also points to similarities in the circuitries regulating self-renewal of differentiated cells. Taken together, our work emphasizes the power of global temporal analyses of transcription factor occupancy to elucidate mechanisms regulating dynamic biological processes in complex higher organisms.